Explosive Behavior in COVID-19 and Policy Responses: Lessons Learned for Public Health Management - Gündüz, Lokman; Aysan, Ahmet Faruk; Bağcı, Rıfgı Buğra; Karahan, Hatice (Sage, 2024)
Since the first case of COVID-19 in Turkey, there has been a lingering question as elsewhere in the world: ‘‘When will or should the government impose severe restrictions to protect public health?’’ From a public health perspective, there is value in developing a model to support proactive implementation of social policies. This study aimed to show the benefits of using a novel econometric test (the Generalized Supremum Augmented Dickey-Fuller Test) to detect explosive behavior (bubbles) in Turkey’s daily COVID-19 cases and deaths. Results from the analysis demonstrated a link between identified explosive episodes and critical public health decisions, especially in the case of daily new deaths. They also showed a negative relationship between the formation of exuberant behavior during the pandemic and the vaccination rate. Public health policymakers can incorporate this method into their arsenal to evaluate the overall health situation in combating the pandemic and respond accordingly. Furthermore, among the lessons learned from the Turkish experience is the importance of having a coronavirus scientific advisory board in the decision-making process and the ability to promptly implement policy measures.
Keywords: COVID-19; Bubble; Explosive behavior; Public health management; Public policy; Information processing; Time series